2017
DOI: 10.1007/s13304-017-0437-9
|View full text |Cite
|
Sign up to set email alerts
|

Posterior retroperitonoscopic adrenalectomy; a back door access with an unusually rapid learning curve

Abstract: Posterior retroperitonoscopic adrenalectomy (PRA) has become a standard approach to the adrenal gland. The aim of this study was to report an initial experience with the procedure following a proper preparatory phase highlighting the rapidity, safety and effectiveness by which it could be introduced into a surgeon's practice. Between May 2015 and July 2016, 14 PRAs were performed in 14 patients (9 females and 5 males). The average age was 46 years, BMI: 25.5 kg/m, and ASA score: 2. Indications included: incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Bacalbasa et al [ 11 ] reported the case of a 65-year-old patient treated with a complete resection en bloc with left nephrectomy and adrenalectomy, distal pancreatectomy, splenectomy, left colectomy, and para-aortic lymph node dissection. In the modern pursuit of minimally invasive technology with respect to aesthetics, posterior retroperitonoscopic adrenalectomy (PRA) has become a standard approach for removal of the adrenal gland [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacalbasa et al [ 11 ] reported the case of a 65-year-old patient treated with a complete resection en bloc with left nephrectomy and adrenalectomy, distal pancreatectomy, splenectomy, left colectomy, and para-aortic lymph node dissection. In the modern pursuit of minimally invasive technology with respect to aesthetics, posterior retroperitonoscopic adrenalectomy (PRA) has become a standard approach for removal of the adrenal gland [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…For retroperitoneoscopic approach, the pressure is usually set at 18-25 mmHg to provide a sufficient operating space. Despite this, the retroperitoneoscopic approach has been reported to have a rapid learning curve (37).…”
Section: Laparoscopic Versus Retroperitoneoscopic Approachesmentioning
confidence: 99%